Colonic Ulcerations Associated with Diclofenac Treatment - Bernd Schönberger; Stephan Nickl; Franzjosef Schweiger (Canadian Journal of Gastroenterology)
Nonsteroidal anti-inflammatory drugs frequently exert toxic effects on the upper gastrointestinal mucosa. However, inflammation and ulcerations in the colon secondary to these agents have been increasingly recognized in recent years. A patient presenting with abdominal pain, weight loss and diarrhea while taking a slow release form of diclofenac sodium (Voltaren SR; Ciba-Geigy) is described. Extensive ulcerations in the right colon and healing upon discontinuation of the drug are documented by colonoscopy.